Video of the Month: Pulsating Umbilicus in a Neonate with Left Ventricular Diverticulum - Moormann, M.; Vollroth, M.; Lacher, M.; Stepan, H.; Gräfe, D.; Thome, U.; Rützel, S.; Weidenbach, M.; Martynov, I.; Pügge, C. (European Journal of Pediatric Surgery Reports, 2024)
Left ventricular diverticulum (LVD) is a rare malformation presenting in 0.05% of all congenital cardiac anomalies. It is associated with additional cardiac and extracardiac malformations. We report on a female neonate with prenatally diagnosed heterotaxia and dextrocardia who was born with a pulsating supraumbilical mass. Echocardiography revealed a diverticulum originating from the left ventricle, which was connected to the umbilicus. Magnetic resonance imaging confirmed an LVD without evidence of a diaphragmatic hernia on the day of life 9. The child underwent laparotomy/lower sternotomy, and the diverticulum and epigastric hernia were closed. The postoperative course was uneventful, and the girl was discharged on the 10th postoperative day. In a neonate with a pulsatile supraumbilical mass, the diagnosis of a congenital LVD should be taken into consideration. The treatment is straightforward and was successful in this single case.
Keywords: left ventricular diverticulum; pulsating umbilicus; pentalogy of Cantrell